ENERGETICS OF ANHYDRITE, BARITE, CELESTINE, AND ANGLESITE: A HIGH-TEMPERATURE AND DIFFERENTIAL SCANNING CALORIMETRY STUDY - Majzlan J.; Navrotsky A.; Neil J.M. (My University, 2002)
The thermochemistry of anhydrous sulfates (anglesite, anhydrite, arcanite, barite, celestine) was investigated by high-temperature oxide melt calorimetry and differential scanning calorimetry. Complete retention and uniform speciation of sulfur in the solvent was documented by (a) chemical analyses of the solvent (3Na2O . 4MoO3) with dissolved sulfates, (b) Fourier transform infrared spectroscopy confirming the absence of sulfur species in the gases above the solvent, and (c) consistency of experimental determination of the enthalpy of drop solution of SO3 in the solvent. Thus, the principal conclusion of this study is that high-temperature oxide melt calorimetry with 3Na2O . 4MoO3 solvent is a valid technique for measurement of enthalpies of formation of anhydrous sulfates. Enthalpies of formation (in kJ/mol) from the elements (ΔHf°) were determined for synthetic anhydrite (CaSO4) (-1433.8 +/- 3.2), celestine (SrSO4) (-1452.1 +/- 3.3), anglesite (PbSO4) (-909.9 +/- 3.4), and two natural barite (BaSO4) samples (-1464.2 +/- 3.7, -1464.9 +/- 3.7). The heat capacity of anhydrite, barite, and celestine was measured between 245 and 1100 K, with low- and high-temperature Netzsch (DSC-404) differential scanning calorimeters. The results for each sample were fitted to a Haas-Fisher polynomial of the form Cp(245 K < T < 1100 K) = a + bT + cT-2 + dT-0.5 + eT2. The coefficients of the equation are as follows: for anhydrite a = 409.7, b = -1.764 x 10-1, c = 2.672 x 106, d = -5.130 x 103, e = 8.460 x 10-5; for barite, a = 230.5, b = -0.7395 x 10-1, c = -1.170 x 106, d = -1.587 x 103, e = 4.784 x 10-5; and for celestine, a = 82.1, b = 0.8831 x 10-1, c = -1.213 x 106, d = 0.1890 x 103, e = -1.449 x 10-5. The 95% confidence interval of the measured Cp varies from 1 to 2% of the measured value at low temperature up to 2 to 5% at high temperature. The measured thermochemical data improve or augment the thermodynamic database for anhydrous sulfates and highlight the remaining discrepancies.